Asymmetric shocks and adjustment in West African Monetary Union - DEDEHOUANOU, SENAKPON FIDÈLE ANGE (My University, 2009)
This paper studies the adjustment to asymmetric shocks of Western African economies using SVAR and State Space models. This concern is justified by the economic environment of West Africa which is characterized by the shocks. Studies focusing on the asymmetric shocks criterion refer to the theoretical framework of Optimal Currency Areas without going beyond the real issue of adjustment as raised by the theory. This research identifies and determines the nature of macroeconomic shocks in the West African Monetary Union. Based on these results, it evaluates the usefulness of potential off market adjustment mechanisms. Several implications for economic policies are deduced, particularly in the present context of regional integration.
Keywords: Monetary Union; Asymmetry Shocks; Adjustment; Fiscal Policy; SVAR; Insurance Mechanism